Future prospects for International Pacific Cooperation : proceedings of the International Symposium on the Pacific Ocean (Tokyo, 1977)
Utilization and development of the Pacific Ocean : future prospects for international Pacific cooperation : proceedings of the International Symposium on the Pacific Ocean November 30-December 2, 1976, Japan Shipping Club, Tokyo, Japan.
Keywords: Tài nguyên biển,Marine resources